Implementing Child-Friendly Schools Program at Muhammadiyah Elementary School in South Tangerang - Suharsiwi Suharsiwi; Rusydy Sjakyakirti Arifin; Anis Setiyanti; Muhammad Arvan (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
Child-Friendly Schools (CFS) are formal and non-formal education units that are safe, clean, healthy, and environmentally friendly. Schools guarantee, fulfill and respect children's rights and protect them from violence and discrimination. This child-friendly school model has proven effective in protecting children's rights, preventing discrimination, violence, and other unwanted actions, and developing students' potential. This study uses a qualitative descriptive approach to determine the implementation of the child-friendly school program at Muhammadiyah Elementary School in South Tangerang. Data collection in this study was conducted by conducting interviews with school principals and teachers, observing the teachers' and students' activities while at school, and studying school written documentation. To increase the trust, researchers conducted triangulation by examining field observation notes, written documents, and interview transcripts. Based on the study's findings and the discussion of the results, it was evident that Muhammadiyah Elementary School in South Tangerang has successfully implemented a child-friendly school program, despite needing to be officially designated. The school fulfills at least four of the six indicators required for implementing child-friendly schools, as outlined in PPPA Regulation 8 of 2014. These indicators include having a child-friendly school policy; incorporating child-friendly learning approaches; providing training for teachers and education administration staff on child rights; and ensuring child-friendly infrastructure and facilities are in place.